Collaborative convergence and virtual teamwork for organizational transformation - Zhao, Jingyuan, 1968- (IGI Global, 2021)
"This book addresses the design and implementation of e-collaboration technologies, and their use in business today establishing the important links between the use of e-collaboration technologies and behavioral patterns in the workplace"--